2020
DOI: 10.1002/1873-3468.13783
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between ubiquitin and yeast polymerase η C terminus does not require the UBZ domain

Abstract: Edited by Claus AzzalinPolymerase g (Polg) is one of the Y-family polymerases that is recruited by monoubiquitinated proliferating cell nuclear antigen (Ub-PCNA) to DNA damage sites during translesion synthesis (TLS). This interaction is mediated by an ubiquitin-binding zinc-finger (UBZ) domain and a PCNA-interacting protein (PIP) box in Polg, which binds to ubiquitin and PCNA, respectively. Here, we show that without the UBZ domain, the PIP box of yeast Polg has a novel binding function with ubiquitin. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The PIP box is well characterized for Polη’s interaction with PCNA ( 5 , 26 , 49 ). A recent NMR study suggested that the PIP box in yeast Polη also contributes to its interaction with Ub ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PIP box is well characterized for Polη’s interaction with PCNA ( 5 , 26 , 49 ). A recent NMR study suggested that the PIP box in yeast Polη also contributes to its interaction with Ub ( 50 ).…”
Section: Introductionmentioning
confidence: 99%